English language : for cambridge O level - Elsdon, Graham (United kingdom : Cambridge university press, 2022)
"English Language for Cambridge O Level Coursebook (3rd Edition)" by Cambridge University Press is an essential resource for students preparing for the Cambridge O Level English Language exam. It offers clear, structured lessons on reading, writing, speaking, and listening, with a strong focus on skill development and exam preparation. The textbook includes a wide range of practice activities, model answers, and practical exam strategies, ensuring that students are well-prepared to excel in their exam and improve their overall language proficiency.
Keywords: English : Coursebook; O level : 3rd edition